Quality of Upgraded Layer Fed with Different Levels of Annatto Seeds (Bixa orellana L.) as Feed Supplement Raised under Different Housing Conditions - Falculan, Ken (Technium BioChemMed, 2021)
This study was conducted to determine the laying performance and egg quality of upgraded layer fed with different levels of annatto seeds as feed supplement under different housing conditions. The experimental method of research using Complete Randomized Design with four treatments in three replications was employed. The data gathered on the different levels of annatto seeds as feed supplement and the different housing conditions for the laying performance and egg quality were analyzed using Analysis of Variance and Duncan Multiple Range Test. The findings implied that the laying performance of upgraded layer was significantly affected by different levels of annatto seeds as feed supplement and has comparable effect on length, color, and weight of yolk but the weight, width, weight of albumen and color of yolk were significantly affected. The housing condition did not affect the laying performance and egg quality of the upgraded layer.